2006
DOI: 10.1111/j.1460-9568.2006.04577.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural responses to water surface waves in the midbrain of the aquatic predator Xenopus laevis laevis

Abstract: Many aquatic vertebrates use mechano-sensory lateral lines to decipher water movements. The peripheral and central organization of the lateral line system has much in common with the auditory system. Therefore, it was hypothesized that the information processing of both systems could be related. Analogous to acoustic objects, for instance, object representations along the central lateral line pathway must be generated from patterns of particle motion across peripheral receivers. Thus, the lateral line offers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…It would be intriguing to know whether similar mechanisms are at play in the hindbrain input. For example, in the mature tectum, different populations of cells can be found that respond to either single sensory modalities or to different combinations (Behrend et al 2006;Lowe 1987). In our study, we found that all cells that receive input from retinotectal synapses also receive hindbrain inputs.…”
Section: Open Questions and Future Directionssupporting
confidence: 57%
See 2 more Smart Citations
“…It would be intriguing to know whether similar mechanisms are at play in the hindbrain input. For example, in the mature tectum, different populations of cells can be found that respond to either single sensory modalities or to different combinations (Behrend et al 2006;Lowe 1987). In our study, we found that all cells that receive input from retinotectal synapses also receive hindbrain inputs.…”
Section: Open Questions and Future Directionssupporting
confidence: 57%
“…Much like its mammalian homologue, the superior colliculus, the optic tectum also receives inputs from a variety of different sensory modalities, including a range of mechanosensory inputs carrying somatosensory, auditory, vestibular, and lateralline information (Behrend et al 2006;Lowe 1986Lowe , 1987Munoz et al 1995;Vanegas 1984). In the colliculus, convergence between different sensory inputs can lead to multisensory integration, a process important for enhancing detection, localization, identification, and response to external environmental events (for a review, see Stein et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have described the capability of various aquatic animals, such as fishes and amphibians, to locate the sources of surface waves and subsurface water movements (e.g. Bleckmann et al, 1989;Coombs and Fay, 1993;Behrend et al, 2006;Görner, 1973) and to discriminate between parameters such as stimulus frequency (Bleckmann et al, 1981;Frühbeis, 1984;Elepfandt et al, 1985), amplitude (Waldner, 1981;Coombs and Fay, 1993) and object size (Vogel and Bleckmann, 2001). Furthermore, it has been shown that blind cave fishes are able to identify and discriminate the shape and spatial arrangement of stationary objects by means of lateral-line input (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…THE AMPHIBIAN OPTIC TECTUM, homologous to the mammalian superior colliculus, is a multisensory processing center that receives visual input from the retinal ganglion cells (RGCs) in the eye as well as from nonoptic mechanosensory inputs originating from the somatosensory, lateral line, auditory, and vestibular systems (Behrend et al 2006;Lowe 1986;Munoz et al 1995). The neurons that comprise the optic tectum, collectively referred to as tectal neurons, organize into somatic layers with the deepest layer being the most periventricular and most medial.…”
mentioning
confidence: 99%